(untitled) (Fiep Bulletin - online, 2014)
Detaches-itself in this researches the importance of the Biomechanics in the academic formation of the teachers of Physical Education. The analysis of the human movement, involves the knowledge of the exact sciences, specifically to Mechanical, branch of the Physical one and to Mathematical, however a big difficulty exists for the education of the Biomechanics in the graduation. The objective of this researches, was verify the knowledge of the graduating students about the adequate use of the sporting footwear for the main sports of block, handball, futsal, volleyball and basketball. The sample was composed for 34 students of Physical Education, of different semesters of the Federal University of Pelotas, 19 men and 15 women, with ages varying between 20 and 25 years. It was utilized, as instrument of measure, a questionnaire for the achievement of the interviews. The questionnaire was constituted by questions related to the systems of protection and deaden originating from the specific sporting footwear for each one of these sporting modalities, also were questioned itself received some kind of orientation of the professors, related to this thematic. The facts were grouped utilizing a descriptive statistics, for verify the incidence of them replaced. With base in the results found is able to conclude that new approaches of educational stamp should be elaborate for facilitate the education of the Biomechanics.